(untitled) (Journal of Engineering, 2024)
When multitudes of people need to be evacuated from their homes for various reasons, including natural catastrophes and armed conflicts, time and money are of the essence. Therefore, emergency relief tents are considered the most effective option for this situation. However, the indoor environment of these tent types might be thermally uncomfortable, particularly on hot or extremely cold days. Different techniques were used to overcome this problem including evaporative cooling systems. The present study aims to use a numerical approach to assess the impact of utilizing a two-stage indirect/direct evaporative cooling system on enhancing the interior thermal comfort conditions of the relief tent. The numerical part was done by utilizing software that was written in Fortran language to simulate the case under various parameters, including changing the cellulose pad thickness and the volumetric water flow rates in the second heat exchanger of the indirect cooling stage. The selection of boundary conditions that were applied in numerical analysis was based on experimental data collected over specified days during the summer of 2022, in particular from July 15th to September 15th. According to the findings, having two heat exchangers in the indirect cooling stage of the cooling system helps keep the tent model at a comfortable temperature because of the exceptional performance of the proposed cooling system in lowering both dry and wet bulb air temperatures before entering the direct evaporative cooling stage. In addition, it was found that the indoor temperature drop increased by about 19% when increasing the thickness of the cellulose pad and raising the water flow rate in the second heat exchanger of the indirect cooling stage.